Data for - Investigation of post-weld rolling methods to reduce residual stress and distortion - Colegrove, Paul; Cozzolino, Daniel (Cranfield University, 2017)
Data set containing the results from models that predict residual stress and distortion after rolling.
Keywords: welding mechanism; Finite Element model; Residual stresses; distortions; Materials Engineering not elsewhere classified